THE AGE OF THE INNER CORE - Labrosse S.; Poirier J.P.; Le Mouel J.L. (My University, 2001)
The energy conservation law, when applied to the Earth's core and integrated between the onset of the crystallization of the inner core and the present time, gives an equation for the age of the inner core. In this equation, all the terms can be expressed theoretically and, given values and uncertainties of all relevant physical parameters, the age of the inner core can be obtained as a function of the heat flux at the core-mantle boundary and the concentrations in radioactive elements. It is found that in absence of radioactive elements in the core, the age of the inner core cannot exceed 2.5 Ga and is most likely around 1 Ga. In addition, to have an inner core as old as the Earth, concentrations in radioactive elements needed in the core are too high to be acceptable on geochemical grounds.
Keywords: CORE; INNER CORE; THERMAL EVOLUTION